Defining the Emerging Blood System During Development at Single-Cell Resolution - Karlsson, Göran; Sommarin, Mikael N. E.; Böiers, Charlotta (Frontiers in Cell and Developmental Biology, 2021)
Developmental hematopoiesis differs from adult and is far less described. In the developing embryo, waves of lineage-restricted blood precede the ultimate emergence of definitive hematopoietic stem cells (dHSCs) capable of maintaining hematopoiesis throughout life. During the last two decades, the advent of single-cell genomics has provided tools to circumvent previously impeding characteristics of embryonic hematopoiesis, such as cell heterogeneity and rare cell states, allowing for definition of lineage trajectories, cellular hierarchies and cell-type specification. The field has rapidly advanced from microfluidic platforms and targeted SC-qPCR, to high throughput unbiased single-cell transcriptomic analysis, single-cell chromatin analysis, and cell tracing – offering a plethora of tools to resolve important questions within hematopoietic development. Here we describe how these technologies have been implemented to address a wide range of aspects of embryonic hematopoiesis ranging from the gene regulatory network of dHSC-formation via endothelial to hematopoietic transition (EHT) and how EHT can be recapitulated in vitro, to hematopoietic trajectories and cell fate decisions. Together, these studies have important relevance for regenerative medicine and for our understanding of genetic blood disorders and childhood leukemias.